2017
DOI: 10.1177/0017896917691789
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a structured education intervention for Latinas concerning breast cancer and mammography

Abstract: Objective: This study examined the utility of living room and church-based small group educational sessions on breast cancer and mammography, for under-served Latinas in North Carolina, USA. Design: Non-randomised, single arm design. Setting: A total of 329 self-selected Latinas participated in 31 small group educational classes in church and home locations in rural and urban settings, and underwent pre- and post-intervention testing of knowledge about breast cancer and mammography. Method: Participants comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Culturally geared interventions have shown to increase BC screening and knowledge (Meneses, Gisiger-Camata, Schoenberger, Weech-Maldonado, & McNees, 2015; Shirazi, Shirazi, & Bloom, 2015). Despite the effectiveness of such interventions (Laughman et al, 2017; Ramiirez et al, 2014), the women in our sample struggled to find the resources they feel would have provided aid during their BC. Women expressed the need for an online community with doctors and program references in their areas and the ability to interact with other women who are going through a similar process or who have already gone through it.…”
Section: Discussionmentioning
confidence: 96%
“…Culturally geared interventions have shown to increase BC screening and knowledge (Meneses, Gisiger-Camata, Schoenberger, Weech-Maldonado, & McNees, 2015; Shirazi, Shirazi, & Bloom, 2015). Despite the effectiveness of such interventions (Laughman et al, 2017; Ramiirez et al, 2014), the women in our sample struggled to find the resources they feel would have provided aid during their BC. Women expressed the need for an online community with doctors and program references in their areas and the ability to interact with other women who are going through a similar process or who have already gone through it.…”
Section: Discussionmentioning
confidence: 96%
“…Significantly greater mean change in self-efficacy to discuss FHH with family members and doctors (0.66[SD = 1.4] vs 0.24[SD = 1.0], p = 0.0003 and 0.69[SD = 1.3] vs 0.30[SD = 1.1], p = 0.0008; respectively. No significant difference in posttest mean knowledge score 2 community health centers in Oakland, CA and Washington, DC Laughman 2017 [ 35 ] In-person Education Culturally sensitive health education classes hosted by certified bilingual Latina health educator regarding breast cancer and mammography None Pretest–Posttest Design Underserved adult female Latinas in North Carolina without history of breast cancer Questionnaire developed by researchers Prepost results varied depending on the three major themes: risk factors, screening and signs and symptoms. Of the 25 total questions, 15 (60%) showed statistically significant improvement in correct response rate, 8 showed nonstatistically significant improvement, and no question showed statistically significant worsening.…”
Section: Resultsmentioning
confidence: 99%
“…Linguistic and culturally concordant care, including cultural competency training for providers, has also repeatedly been identified as a successful strategy for increasing HL among immigrant populations generally [ 18 ]. Furthermore, successful interventions often consider the opinions of the target population when designing content to ensure that the experience is culturally relevant [ 16 , 28 , 29 , 34 , 35 , 40 , 44 , 45 , 55 , 62 , 65 , 73 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on the effectiveness of a breast and cervical cancer screening promotion program (Cultivando La Salud) for low-income Latinas with a CHW intervention found no significant differences in BC knowledge between the intervention and control groups after 6 months (Fernandez et al, 2009). Another study that assessed the effects of group educational sessions for Latinas in North Carolina compared BC knowledge (risk factors, screening, signs and symptoms) at baseline, postintervention, and 3 months—the authors found the postintervention increases in BC risk factor knowledge were only somewhat sustained after 3 months (Laughman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%